PRODUKSI PEKTIN DARI KULIT BUAH COKLAT (Theobroma Cacao) (The production pectin from Cacao leather) (Jurnal Teknologi Pangan, 2013)
The progress and development of the industry in Indonesia is increasing demand for pectin. Indonesia is  a  country rich  in agricultural crops, one of  cacao. This  cacao leather is the only waste that can not be used. In this study are described on the extraction of pectin  from  waste  chocolate  skin.  Pectin    is  an  important    component  in  the  food  industry, cosmetics  and  medicines.  The  research  using  two  variables,    time  (200,225,250,275,300 minutes),and   the  ratio  of  solvent  (1:8,1;  10,1:12,1:16,1:16)l.The  results  obtained  on  the condition of  the maximum time of 250 minutes and  a solvent ratio of 1:12. The yield of weight of pectin was 16.23%Keywords : Cocoa skin, Pectin, extraction